"When you're down, stay down": A lesson for all competitive alpine skiers supported by an ACL rupture measured in vivo - Jörg Spörri; Erich Müller; Josef Kröll (Elsevier, 2022)
Background: During an experiment, a ski racer equipped with various measurement devices suffered an anterior cruciate ligament (ACL) rupture in his right knee. The aim of this study was to describe the underlying injury mechanism from a functional perspective. Methods: Eight giant slalom turns (i.e., 4 left turns), followed by 1 left turn at which the ACL injury occurred, were recorded by 2 video cameras, electromyography of 4 relevant muscle groups, inertial measurement units to measure knee and hip angles, and pressure insoles to determine ground reaction forces. Results: Due to a loss of balance, the ski racer began to slide sideways at the apex of a left turn. During sliding, his right (outside) leg was actively abducted upward without touching the ground. The ski racer then attempted to stand up again by dropping his leg back towards the snow surface. The end of this dropping was accompanied by a decrease in electromyographic activity in the knee stabilizing muscles. Once the inside edge of the outer ski caught the snow surface, a rapidly increasing peak force, knee flexion, and an aggressive sudden activation of the vastus medialis muscle were observed, while biceps femoris and rectus femoris further decreased their activation levels. This likely resulted in excessive anterior translation of the tibia relative to the femur, causing damage to the ACL. Conclusion: Our example emphasizes that ski racers should not get up until they stop sliding. Remember: "When you're down, stay down."